Diselenide-bond replacement of the external disulfide bond of insulin increases its oligomerization leading to sustained activity - Kenta Arai; Masaki Okumura; Young-Ho Lee; Hidekazu Katayama; Kenji Mizutani; Yuxi Lin; Sam-Yong Park; Kaichiro Sawada; Masao Toyoda; Hironobu Hojo; Kenji Inaba; Michio Iwaoka (Communications Chemistry, 2023)
Abstract Seleno-insulin, a class of artificial insulin analogs, in which one of the three disulfide-bonds (S-S’s) of wild-type insulin (Ins) is replaced by a diselenide-bond (Se-Se), is attracting attention for its unique chemical and physiological properties that differ from those of Ins. Previously, we pioneered the development of a [C7UA,C7UB] analog of bovine pancreatic insulin (SeIns) as the first example, and demonstrated its high resistance against insulin-degrading enzyme (IDE). In this study, the conditions for the synthesis of SeIns via native chain assembly (NCA) were optimized to attain a maximum yield of 72%, which is comparable to the in vitro folding efficiency for single-chain proinsulin. When the resistance of BPIns to IDE was evaluated in the presence of SeIns, the degradation rate of BPIns became significantly slower than that of BPIns alone. Furthermore, the investigation on the intermolecular association properties of SeIns and BPIns using analytical ultracentrifugation suggested that SeIns readily forms oligomers not only with its own but also with BPIns. The hypoglycemic effect of SeIns on diabetic rats was observed at a dose of 150 μg/300 g rat. The strategy of replacing the solvent-exposed S-S with Se-Se provides new guidance for the design of long-acting insulin formulations.